ABO‐Incompatible Living Kidney Transplants: Evolution of Outcomes and Immunosuppressive Management. Issue 3 (10th November 2015) - Okumi, M.; Toki, D.; Nozaki, T.; Shimizu, T.; Shirakawa, H.; Omoto, K.; Inui, M.; Ishida, H.; Tanabe, K.
Abstract : ABO‐incompatible living kidney transplantation (ABO‐ILKT) has steadily become more widespread. However, the optimal immunosuppressive regimen for ABO‐ILKT remains uncertain. We aimed to determine the longitudinal changes in the outcomes from ABO‐ILKT compared with those from ABO‐compatible living kidney transplantation (ABO‐CLKT) over the last 25 years. Of 1195 patients who underwent living kidney transplantations (LKT) at our institute between 1989 and 2013, 1032—including 247 ABO‐ILKT and 785 ABO‐CLKT cases—were evaluated for graft survival, patient survival, infectious adverse events, and renal function. The patients were divided into four groups according to the transplantation era and ABO‐compatibility. In the past decade, ABO‐ILKT and ABO‐CLKT recipients yielded almost equivalent outcomes with respect to the 9‐year graft survival rates, which were 86.9% and 92.0%, respectively (hazard ratio [HR] 1.38, 95% confidence interval [CI] 0.59–3.22, p = 0.455). The graft survival rate for ABO‐ILKT conducted between 2005 and 2013 was better than that for ABO‐ILKT conducted between 1998 and 2004 (HR 0.30, 95% CI 0.13–0.72, p = 0.007). ABO‐ILKT recipients showed substantial improvements in the graft survival rate over time. Graft survival was almost identical over the past decade, regardless of ABO‐incompatibility. Currently, ABO‐ILKT is an acceptable treatment for patients with end‐stage renal disease. Abstract : The authors determine the longitudinal changes in the outcomes from ABO‐incompatible living kidney transplantation over the last 25 years and conclude that ABO‐incompatible living kidney transplant recipients have experienced substantial improvements in graft survival rate, frequency of infectious adverse events, and renal function over time.